MADRASAH DI ERA OTONOMI DAERAH - Ahmad Fahroni (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2020)
The implementation of regional autonomy requires the division of governmental functions between the center and the regions, one of the aspects which is a matter between the center and the regions is education. Madrasah as a formal educational institution should receive attention from the government, both the Central Government and local governments, but the problem is that madrasah are institutions under the auspices of the Ministry of Religion, while in the context of autonomy there is a matter that becomes the authority of the central government, namely religious aspects . So that in the course of madrasah are often identified with religious issues, whereas when viewed from the other side of the madrasah is still an educational institution.